Distinct immunohistochemical expression of osteopontin in the adult rat major salivary glands - Obermüller, Nicholas; Gassler, Nikolaus; Gretz, Norbert; Kränzlin, Bettina; Hoffmann, Sigrid; Geiger, Helmut; Gauer, Stefan (Journal of molecular histology, 2006)
Osteopontin is a multifunctional protein secreted by epithelial cells of various tissues. Its expression in the adult rat major salivary glands has not yet been studied. We examined osteopontin expression by immunohistochemistry using a well characterized monoclonal antibody. Submandibular glands of young adult male rats (70-100 days old) showed specific expression in secretion granules of granular duct cells but also in cells of the striated ducts and excretory duct. In the major sublingual as well as the parotid gland expression was found solely in the duct system. In addition, a few interstitial-like cells exhibiting very strong immunostaining for osteopontin could be found in either organ. Expression could neither be seen in acinar cells nor in cells of the intercalated ducts. Moreover, in submandibular glands of more aged rats (6- to 7-month old) which show well developed granular convoluted tubules, there was almost exclusive expression of osteopontin in granular duct cells as well as in some interstitial-like cells, but barely in the striated/excretory duct system. Western blot analysis of the submandibular gland showed a specific band migrating at approximately 74 kDa, detectable at both age stages. Osteopontin secreted fom granular duct cells may influence the compostion of the saliva, e.g. thereby modulating pathways affecting sialolithiasis. Its expression in striated duct cells may also hint to roles such as cell-cell attachment or cell differentiation. The cell-specific expression detected in the rat major salivary glands differs in part from that reported in mice, human and monkey.
Gesehen am 22.06.2022